PENGARUH PEMBINAAN DISIPLIN DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR TARUNA BALAI PENDIDIKAN DAN PELATIHAN ILMU PELAYARAN (BP2IP) TANGERANG - Rosalendro Eddy Nugroho; Waode Sami‟a (Universitas Serang Raya, 2016)
The purpose of this study was to determine the effect of coaching discipline and motivation toward learning achievement cadets Merchant marine Education and Training Institute ( BP2IP ) Tangerang . Respondents are cadets Merchant marine Education and Training Institute ( BP2IP ) Tangerang Youth fifty nine . The method used is distributing .questionnaires to cadets by using Likert scale . Analysis of data using multiple regressionmodels with SPSS . Partial regression analysis found that the variable coaching discipline significantly influence the motivation to learn , and each of the variables showed significant influence on the learning achievement of the Youth cadets Merchant marine Education and Training Institute ( BP2IP ) Tangerang . These results indicate that there is a simultaneous effect between variables influence the development of discipline andmotivation toward learning achievement cadets Merchant marine Education and Training Institute ( BP2IP ) Tangerang.